2017
DOI: 10.1158/1535-7163.mct-17-0341
|View full text |Cite
|
Sign up to set email alerts
|

CCR5-Dependent Homing of T Regulatory Cells to the Tumor Microenvironment Contributes to Skin Squamous Cell Carcinoma Development

Abstract: Squamous cell carcinoma (SCC) is one of the most common human cancers worldwide. Recent studies show that regulatory T cells (Treg) have a critical role in the modulation of an antitumor immune response, and consequently the SCC development. Because the accumulation of Tregs at the tumor site is, in part, due to selective recruitment through CCR5- and CCR5-associated chemokines, we investigated the role of CCR5 in the SCC development. Our findings showed that CCR5-deficient mice (CCR5KO) were efficient in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…We also noted the enhanced expression of chemokines/receptors in interior vs. margin CD8 T cells associated with increased trafficking and infiltration of T cells into the tumor such as Ccl4/5 and receptor Ccr5 (Fig. 4L) [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…We also noted the enhanced expression of chemokines/receptors in interior vs. margin CD8 T cells associated with increased trafficking and infiltration of T cells into the tumor such as Ccl4/5 and receptor Ccr5 (Fig. 4L) [40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…For example, accumulation of CCR5 + myeloid-derived suppressor cells in a mouse model of melanoma is associated with local up-regulation of CCR5 ligands (CCL3/MIP-1α, CCL4/MIP-1β and CCL5/RANTES) 23 . Similarly, regulatory T cells have also been reported to home to a mouse model of cutaneous SCC via CCR5 signalling 24 . In both examples, the CCR5 chemokine signalling pathway is paramount to the immunosuppressive tumour microenvironment 23,24 .…”
Section: Discussionmentioning
confidence: 98%
“…Cutaneous overexpression of CCL22 led to diversion of Tregs from pulmonary melanoma metastases to the skin, leading to inhibition of metastatic growth in the lungs (33). Other studies have shown CCR5-dependent recruitment of Tregs into melanoma and SCC (8, 95), while the ligands for this receptor were produced by MDSCs (8). Consistent with this, CCR5-deficient mice demonstrated slower rate of melanoma growth (8, 95).…”
Section: Immune Evasion By Chemokine Augmentationmentioning
confidence: 97%
“…Other studies have shown CCR5-dependent recruitment of Tregs into melanoma and SCC (8, 95), while the ligands for this receptor were produced by MDSCs (8). Consistent with this, CCR5-deficient mice demonstrated slower rate of melanoma growth (8, 95). In another study, B16 melanoma cells overexpressing CCL21 displayed increased growth potential and on injection induced a more suppressive tumor environment containing increased Tregs and TGFβ but decreased IFN-γ levels (9).…”
Section: Immune Evasion By Chemokine Augmentationmentioning
confidence: 97%